Study on Biolog Identification of Fermenting Yeasts from Fermented Teff (Eragrostis teff (Zucc.)) Dough - Tilahun, Belay; Kassaye, Eyob; Abera, Getaw; Tesfaye, Anteneh; Muleta, Diriba; Bahiru, Andualem; Terefework, Zewdu (New Visions in Biological Science Vol. 7, 2021)
Background: Injera is one of the baked products, which is commonly prepared from teff (Eragrostis teff (Zucc.)) flour. It is a staple food and believed to be consumed on a daily basis by two-thirds of Ethiopians, a population of nearly 100 million. As it is a product of naturally fermented dough, the course of fermentation is done by consortia of microorganisms. Teff injera is getting popular in the developed world because of its gluten free nature and being a whole grain product. Therefore, this study was aimed to isolate and identify yeasts from fermenting Teff (Eragrostis teff) dough. Place and Duration of Study: Samples were collected from different sources in Addis Ababa, Ethiopia. Laboratory isolation and identification of isolates were carried out at Holeta Biotechnology Institute, Microbial Biotechnology laboratory and Ethiopian Institute of Biodiversity, Microbial laboratory from December to April 2015 to June 2016 G. C. Methodology: A total of 200 dough samples were collected from households with different fermentation stages. Twenty (20) yeast isolates with different cultural characteristics were selected and further identified by omnilog identification systems. Results: The seven yeast isolates obtained from teff dough were identified as Pichia fermentans, Pichia spp., Rhodotorula aurantiaca B, Pichia fluxuum, Candida humilis, Trichosporon beigelii B and, Cryptococcus albidus Var aerus Conclusion: This study has confirmed the presence of different yeast in the fermenting teff dough and also supports the involvement of consortia of various groups of microorganisms in the course of the fermentation.